2017
DOI: 10.5433/1679-0359.2017v38n2p1009
|View full text |Cite
|
Sign up to set email alerts
|

Glycerin from biodiesel in the feeding of red-egg layers

Abstract: The aim of this study was to evaluate the effects of vegetable glycerin on performance and egg quality of red-egg layers in the second production cycle. A total of 252 Hy-Line Brown layers weighing 1.919 ± 0.095 kg, at 90 weeks, were used in a completely randomized design with six treatments and seven birds per replication. The experiment lasted 84 days. Treatments consisted of a control diet (no glycerin) and five diets with increasing levels of vegetable glycerin (2, 4, 6, 8, and 10%). The following variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Similarly, the physical characteristics of the eggs were not affected by the experimental treatments (results not presented), which on average, recorded the following values: 0.41 mm in shell thickness, 11.9 in color score, 5.95 mm in albumin height and 89.3 Haugh units. Similar to what was found in this study, the literature concludes that shell thickness, yolk color or the height of the albumin of the eggs are not affected by the levels of glycerin inclusion in the diets (Swiatkiewicz & Koreleski, 2009Boso et al, 2013Duarte et al, 2014;Mandalawi et al, 2015;Cufadar et al, 2016;Fontinele et al, 2017).…”
Section: Treatmentsupporting
confidence: 86%
See 4 more Smart Citations
“…Similarly, the physical characteristics of the eggs were not affected by the experimental treatments (results not presented), which on average, recorded the following values: 0.41 mm in shell thickness, 11.9 in color score, 5.95 mm in albumin height and 89.3 Haugh units. Similar to what was found in this study, the literature concludes that shell thickness, yolk color or the height of the albumin of the eggs are not affected by the levels of glycerin inclusion in the diets (Swiatkiewicz & Koreleski, 2009Boso et al, 2013Duarte et al, 2014;Mandalawi et al, 2015;Cufadar et al, 2016;Fontinele et al, 2017).…”
Section: Treatmentsupporting
confidence: 86%
“…Some authors mention that the (Guerra et al, 2011), however, in this study, the use of crude glycerin with 1.1% sodium did not cause that effect. The increase in egg-laying by using glycerin in diets was reported by Fontinele et al (2017) in brown chickens in the second egg-laying cycle, where birds fed diets containing 10% crude glycerin laid 6% more eggs compared to birds in the control group. Boso et al (2013) observed that egg production of laying hens increased linearly with the consumption of glycerin in a range that varied between 1.5 and 7.5% during the 16 weeks that egg-laying lasted, and this response is directly related to the increase in feed consumption.…”
Section: Treatmentmentioning
confidence: 71%
See 3 more Smart Citations